2018
DOI: 10.1007/s11842-018-9397-2
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the Interest of Forest Owners to Combine Nature-Oriented and Economic Uses of Forests

Abstract: Protecting biodiversity within separate set-aside conservation areas has not been effective enough to halt its loss. Thus, new approaches to conserve biodiversity alongside production are needed. The non-market values of a forest may play an essential role when the forest owner decides the use of their land. However, so far the service offerings other than related to timber production, have been scant. The mismatch between decision support services offered and the service interests of forest owners may result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…"Soft data", such as perception, vision, expectation, preferences of stakeholders and involved actors, are considered particularly relevant in evaluation. In forestry there is a long tradition of studies focusing on forest owners' perceptions and preferences 23 (e.g., amongst the most recent: Pynnönen et al, 2018;Matilainen et al, 2019), as well as stakeholders' opinions (e.g., Focacci et al, 2017;De Meo et al, 2018) which evaluation methods for social innovation can get inspired from. However, among the tools based on primary data that were found in the literature analysis, only a few include the text of questions or questionnaires used for data collection (e.g., Polman, 2002), thus limiting the capacity of practitioners and evaluators to apply and replicate in their own evaluations methods that are proposed by scientists.…”
Section: Type Of Data (Primary/secondary)mentioning
confidence: 99%
“…"Soft data", such as perception, vision, expectation, preferences of stakeholders and involved actors, are considered particularly relevant in evaluation. In forestry there is a long tradition of studies focusing on forest owners' perceptions and preferences 23 (e.g., amongst the most recent: Pynnönen et al, 2018;Matilainen et al, 2019), as well as stakeholders' opinions (e.g., Focacci et al, 2017;De Meo et al, 2018) which evaluation methods for social innovation can get inspired from. However, among the tools based on primary data that were found in the literature analysis, only a few include the text of questions or questionnaires used for data collection (e.g., Polman, 2002), thus limiting the capacity of practitioners and evaluators to apply and replicate in their own evaluations methods that are proposed by scientists.…”
Section: Type Of Data (Primary/secondary)mentioning
confidence: 99%
“…Also Niskanen et al (2007) stated that for some owners, forest as a symbolic asset may be more meaningful than economic profitability. More recently, in a study by Pynnönen et al (2018), forest owner objectives were combined with preferred forest management style and it was found that a large share of forest owners are willing to manage their forests by combining economic and other objectives equally. Table 2.…”
Section: Review Of Forest Owner Objectives Researchmentioning
confidence: 99%
“…Referring to the conservation procedure (Table 3b, recommendations by 65%), studies proposed to enhance the distribution of information regarding conservation (recommended by 59%). Recommendations on how to better reach forest owners ranged from the adaptation of advisory services (Urquhart 2009;Salomaa et al 2016;Pynnönen et al 2018) to different ways to share concrete experiences through peer-learning, or regional demonstrations (Bieling 2004;Van Gossum et al 2005 Gatto et al (2019). Bold numbers show the main direction of influence.…”
Section: Policy Recommendationsmentioning
confidence: 99%